2022
DOI: 10.1007/s00268-022-06562-5
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival Advantage of Omentum Preservation Over Omentectomy for Advanced Gastric Cancer: A Systematic Review and Meta‐Analysis

Abstract: Background Since 1910, omentectomy has been an essential component of radical gastrectomy for advanced gastric cancer. However, researchers have recently questioned the benefit of omentectomy in radical gastrectomy. The aim of this meta-analysis was to compare omentectomy and omentum preservation in gastrectomy for advanced gastric cancer in terms of survival outcomes and short-term outcomes. Methods The PubMed, Embase, Web of Science, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Seven previous meta-analyses studied the oncologic feasibility of PO [ 326 327 328 329 330 ]. All the meta-analyses showed that PO was not inferior to TO regarding OS and relapse-free survival.…”
Section: Surgical Treatment ( Flowchart 3 ...mentioning
confidence: 99%
“…Seven previous meta-analyses studied the oncologic feasibility of PO [ 326 327 328 329 330 ]. All the meta-analyses showed that PO was not inferior to TO regarding OS and relapse-free survival.…”
Section: Surgical Treatment ( Flowchart 3 ...mentioning
confidence: 99%
“…Peritoneal recurrence stood out, representing 36-45% of all kinds [38]. Omentum turned out as the most involved peritoneal site [6,7,14,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Despite omental tissue's protumoral properties, authors are still debating on the need to perform CO, in addition to gastrectomy and D2 lymphadenectomy for GC [6,7,14,[22][23][24][25][26]. Analyses of major guidelines in GC treatment clearly explained this topic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations